Ziyadah, Radwan. “The Crisis of Arab Society in Contemporary Arab Discourse,” Year 14, Issue 56 (Spring 1430 AH/ 2009 CE), Pp. 147-176. - زيادة رضوان (Al-Fikr al-islāmī al-muʿāṣir (previously Islamiyat al-Ma’rifah), 2009)
Radwan Ziyadah’s article presents a methodological approach in studying the crisis of Arab society, and contends that such a methodology has a high diagnostic and interpretive capability on the level of theorization, yet fell short when providing solutions because of its inability to find mechanisms and tools of change consistent with its diagnosis and interpretation. The article discusses factors of civilizational building and examines the origins of some concepts such as civilization and urbanism. It then attempts to present a more interpretive classification to learn the epistemological orientation in contemporary Arab thought. It concludes that the political and social method is the closest association with Arab reality, with the condition of not accepting it as-is but rather to work towards developing its mechanisms.